2021
DOI: 10.1186/s12884-021-04082-z
|View full text |Cite
|
Sign up to set email alerts
|

The association of antenatal D-dimer and fibrinogen with postpartum hemorrhage and intrauterine growth restriction in preeclampsia

Abstract: Background D-dimer and fibrinogen were verified to be altered in preeclampsia. This study was to evaluate the associations of D-dimer and fibrinogen plasma levels with postpartum hemorrhage or intrauterine growth restriction in preeclamptic women. Methods This was a retrospective study that recruited 278 preeclamptic women with singleton pregnancy from January 2016 to December 2019. Patients were allocated into five groups: mild preeclampsia (mPE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Damaged vascular endothelium and imbalances in the three major systems including the coagulation, anticoagulation, and fibrinolysis are currently thought to be related to the incidence of PE [ 18 , 21 , 22 ]. Several studies [ [23] , [24] , [25] ] have shown that coagulation-related indicators alter in PE-affected women, however conventional coagulation tests only provide data on a specific, discrete element of the coagulation process, which is insufficient for comprehending the entire coagulation process. By contrast, the Sonoclot coagulation analyzer can rapidly and conveniently monitor the entire coagulation process in a small amount of serum [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damaged vascular endothelium and imbalances in the three major systems including the coagulation, anticoagulation, and fibrinolysis are currently thought to be related to the incidence of PE [ 18 , 21 , 22 ]. Several studies [ [23] , [24] , [25] ] have shown that coagulation-related indicators alter in PE-affected women, however conventional coagulation tests only provide data on a specific, discrete element of the coagulation process, which is insufficient for comprehending the entire coagulation process. By contrast, the Sonoclot coagulation analyzer can rapidly and conveniently monitor the entire coagulation process in a small amount of serum [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancies in twins are particularly susceptible to HDP, and it makes PPH more at risk [20]. HDP causes spasms of systemic small blood vessels, and abnormal blood flow to the uterine placenta, leading to uterine myxedema, in addition, antihypertensive drugs in the clinic may reduce the excitability of uterine muscle fibers, leading to compromised uterine contractile function and increased PPH risk.…”
Section: Discussionmentioning
confidence: 99%
“…Without effective control and treatment, severe cases may lead to convulsions, coma, and even maternal and infant death (Wang et al 2019b). The worldwide incidence of HDP is about 4.6%, which is one of the main reasons that affect the health and mortality of pregnant women and perinatal infants (Shao et al 2021). According to the study, HDP patients and their offspring have significantly increased incidence of cardiovascular and nervous system diseases compared with normal pregnant women (Hou et al 2020).…”
Section: Introductionmentioning
confidence: 97%